Crumbs and the apical spectrin cytoskeleton regulate R8 cell fate in the Drosophila eye. - Pojer, J.M.; Saiful Hilmi, A.J.; Kondo, S.; Harvey, K.F. (PLoS Genetics, 2021)
The Hippo pathway is an important regulator of organ growth and cell fate. In the R8 photoreceptor cells of the Drosophila melanogaster eye, the Hippo pathway controls the fate choice between one of two subtypes that express either the blue light-sensitive Rhodopsin 5 (Hippo inactive R8 subtype) or the green light-sensitive Rhodopsin 6 (Hippo active R8 subtype). The degree to which the mechanism of Hippo signal transduction and the proteins that mediate it are conserved in organ growth and R8 cell fate choice is currently unclear. Here, we identify Crumbs and the apical spectrin cytoskeleton as regulators of R8 cell fate. By contrast, other proteins that influence Hippo-dependent organ growth, such as the basolateral spectrin cytoskeleton and Ajuba, are dispensable for the R8 cell fate choice. Surprisingly, Crumbs promotes the Rhodopsin 5 cell fate, which is driven by Yorkie, rather than the Rhodopsin 6 cell fate, which is driven by Warts and the Hippo pathway, which contrasts with its impact on Hippo activity in organ growth. Furthermore, neither the apical spectrin cytoskeleton nor Crumbs appear to regulate the Hippo pathway through mechanisms that have been observed in growing organs. Together, these results show that only a subset of Hippo pathway proteins regulate the R8 binary cell fate decision and that aspects of Hippo signalling differ between growing organs and post-mitotic R8 cells.